I was trying to find the value of : $$1+11+111+\cdots+111\cdots11$$ using generating functions instead of using GP. I know that it's going to be same at the end, but still, just for the sake of it, I was trying.

The recurrence I'm using is $a_{n+1}=10a_n+1;~ n\geq 0$ with $a_0=1$.

For the generating series to be— $$A(x)=a_0+a_1x+a_2x^2+\cdots$$, we have, after calculation, $A(x)=\frac{1}{10x^2-11x+1}=\frac{1}{9}\left(\frac{1}{\frac{1}{10}-x}-\frac{1}{1-x}\right)$. (I hope this is correct)

Now, I expanded it using Taylor Series but then, I think something has gone wrong or I did something wrong in the later steps.

  • $\begingroup$ The brackets are the floor function or only brackets? $\endgroup$
    – ajotatxe
    Dec 12, 2017 at 17:22
  • $\begingroup$ @ajotatxe Just simple brackets. Nvm, edited. $\endgroup$ Dec 12, 2017 at 17:24
  • $\begingroup$ What you did is just fine. The Taylor series of your function at $0$ is indeed$$1+11x+111x^2+1\,111x^3+\cdots$$as you wished. $\endgroup$ Dec 12, 2017 at 17:27
  • $\begingroup$ @JoséCarlosSantos Yes, and now how to extract the $a_i$'s from the function? $\endgroup$ Dec 12, 2017 at 17:28

1 Answer 1


You have

$$\sum_{n\geq 0}a_{n}x^{n}\equiv A\left(x\right)=\frac{1}{10x^{2}-11x+1}=\frac{1}{9}\left(\frac{10}{1-10x}-\frac{1}{1-x}\right)=\\=\frac{1}{9}\sum_{n\geq 0}\Big[10\left(10x\right)^{n}-x^{n}\Big]=\sum_{n\geq0}\frac{10^{n+1}-1}{9}x^{n}$$



which is correct.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.